2018
DOI: 10.5812/jjhs.79916
|View full text |Cite
|
Sign up to set email alerts
|

The Requirements and baises of Medical Tourism Website for Hospitals: A Cross-Sectional Study

Abstract: Background: Informing the target population plays an important role in medical tourism attraction and should be managed in order to incorporate all appropriate tools to increase it. The aim of this study was to determine the requirements and basis of a medical tourism website for hospitals. Methods: This study was a cross sectional analytical study that was performed during year 2018 amongst hospital managers and faculty members of Iranian medical sciences universities that have the potential to attract medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Studies have also demonstrated that AR provided a motivational drive during remote learning [16]. A scoping review of 21 articles indicated that professionals and students from different medical specialities trained via VR demonstrated a higher level of accuracy in their medical practice [17].…”
Section: Ar and Vr Applications In Higher Educationmentioning
confidence: 99%
“…Studies have also demonstrated that AR provided a motivational drive during remote learning [16]. A scoping review of 21 articles indicated that professionals and students from different medical specialities trained via VR demonstrated a higher level of accuracy in their medical practice [17].…”
Section: Ar and Vr Applications In Higher Educationmentioning
confidence: 99%
“…Studies show that health information has been one of the most useful and favorite titles of internet users and every day many users around the world visit the websites of health care centers to get health information [5]. Medical tourists search for reliable, accessible, up-to-date and comprehensive information on these websites [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a scarcity of academic exploration into MTF competencies. A lot of research has been done on their roles [ [10] , [11] , [12] , [13] ] as well as their digital presence [ [14] , [15] , [16] , [17] ], legal issues [ [18] , [19] , [20] ], influential factors [ 21 , 22 ], and impact on patients [ 3 , 10 , 23 , 24 ]. Yet, the analysis of MTF competencies within a holistic model is significantly missing.…”
Section: Introductionmentioning
confidence: 99%